2022
DOI: 10.3390/ijms232012376
|View full text |Cite
|
Sign up to set email alerts
|

Role of B Lymphocytes in the Pathogenesis of NAFLD: A 2022 Update

Abstract: Non-alcoholic fatty liver disease and its related complications are becoming one of the most important health problems globally. The liver functions as both a metabolic and an immune organ. The crosstalk between hepatocytes and intrahepatic immune cells plays a key role in coordinating a dual function of the liver in terms of the protection of the host from antigenic overload as a result of receiving nutrients and gut microbiota antigenic stimulation via facilitating immunologic tolerance. B cells are the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…MSCs can also reverse the fibrosis process and lobular inflammatory infiltration in MAFLD mice induced by high-fat diet (HDF) by inhibiting CD4+ T cell proliferation [18]. B cells can mediate liver injury and fibrosis and further promote the development of NASH to fibrosis [56]. Corcione et al [57] found that MSCs may secrete soluble factors through paracrine pathway to arrest the cell cycle of B cells in G0/G1 and inhibit the proliferation of B cells.…”
Section: Immunomodulatory Effect Of Mscsmentioning
confidence: 99%
“…MSCs can also reverse the fibrosis process and lobular inflammatory infiltration in MAFLD mice induced by high-fat diet (HDF) by inhibiting CD4+ T cell proliferation [18]. B cells can mediate liver injury and fibrosis and further promote the development of NASH to fibrosis [56]. Corcione et al [57] found that MSCs may secrete soluble factors through paracrine pathway to arrest the cell cycle of B cells in G0/G1 and inhibit the proliferation of B cells.…”
Section: Immunomodulatory Effect Of Mscsmentioning
confidence: 99%
“…190,191 Chronic inflammation is central to NAFLD disease progression and involves both residential and circulating immune cells, including macrophages and lymphocytes. 192,193 The interaction between the different cell types also involves a slew of inflammatory chemokines and cytokines, such as chemokine (C-C motif) ligand 2 (CCL-2), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β), interleukin-17 (IL-17), and interleukin-18 (IL-18). [194][195][196][197] The treatment of fatty liver disease currently consists of lifestyle recommendations, including regulating calorie intake and exercise.…”
Section: Nonalcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…In addition, gut microbes have been reported to be involved in the development of NAFLD via the regulation of bile acid metabolism, lipid handling, and endotoxin and metabolite production in the gut [ 165 , 166 ]. Chronic inflammation is central to NAFLD disease progression and involves both residential and circulating immune cells, including macrophages and lymphocytes [ 167 , 168 ]. Interactions among the different cell types also involve a slew of inflammatory chemokines and cytokines, such as chemokine ligand 2, tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), IL-1β, IL-17, and IL-18 [ 169 - 172 ].…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…For example, the ratios of regulatory T cells (Tregs) with T helper 1 (Th1) cells, Th17, and CD8 T cells are increased in the pathogenesis of NAFLD, NASH, fibrosis, and NASH-associated HCC [16,131]. Recent studies have also demonstrated that CD4 -CD8double negative T cells make an important contribution to NAFLD and NASH [132,133]. B cells play dual roles in diet-induced NAFLD by secreting cytokines and antibodies, a phenomenon that was reviewed in a recent literature report [134].…”
Section: Inflammation Of Liver Innate and Adaptive Immune Cellsmentioning
confidence: 99%